72.3k views
1 vote



n
=
1

4
(
1
3
)
n

1

1 Answer

5 votes

Answer:

6

Explanation:

The correct notation is: Summation from n = 1 to infinity of the expression:


4((1)/(3) )^(n-1)

If we expand this notation, we will find that the given summation represent the terms of a G.P and we have to find the sum of infinite terms of a G.P. By placing n=1,2,3,4,... we can find the first few terms as shown below:


4((1)/(3) )^(1-1)=4\\\\ 4((1)/(3) )^(2-1)=4((1)/(3) ) \\\\ 4((1)/(3) )^(3-1) =4((1)/(3) )^(2)

Its obvious from the above result, that the given summation represent a G.P with first term equal to 4 and common ratio of 1/3. The formula of infinite G.P is:


S=(a_(1) )/(1-r)

Using the value of a1 = 4 and r = 1/3 we can calculate the given summation


S=(4)/(1-(1)/(3) )=6

Therefore, the given summation is equal to 6.

User Art Gillespie
by
6.1k points